Study on influence of micro-pitting on non-repetitive run-out of high-precision ball bearings. (August 2022) - Yang, Zhaohui; Li, Chonghe; Zhou, Ningning; Yang, Xiaojun
Highlights: Micro-pitting is simulated by laser processing method. A new evaluate method and criterion for rotation accuracy analysis of high-precision ball bearing caused by micro-pitting. Abstract: The high-precision ball bearing is fundamental to the performance of complex mechanical systems. As the working condition extremely, the micro-pitting become a key problem to influence the rotational accuracy of bearing. This paper developed an experimental method to analyze the relationship between the micro-pitting on the surface of inner groove and the rotational accuracy of bearing, the non-repetitive run-out (NRRO) is applied for rotational accuracy evaluating. In this method, the laser processing method is used to simulate micro-pitting on the surface of inner groove and the laser scanning confocal microscope is used to measure dimension of micro-pitting. Then, the high-precision instrument is applied to measure the values of NRRO with different rotational speeds and loads. Finally, the influence of a micro-pitting for NRRO under different speeds and loads are analyzed for bearing failure predicting. In the future, the NRRO with different micro-pitting size will be measured for failure prediction.